The Implementation of Worksheet Application in Review of Regional Government Financial Report (Case Study at Karangnyar Regency Inspectorate) - Vidia Ayu Satyanovi; Nurul Lujain; Rihan Mustafa ZAHRI (International Journal of Business and Quality Research, 2023)
The purpose of this study was to find out and evaluate the application of Worksheet Application in the Review of Regional Government Financial Report at the Inspectorate of Karanganyar Regency. This type of research is descriptive qualitative. The data collection techniques in this study were through observation, documentation and interviews. The Result shows that the implementation of the Regional Government Financial Report review with Worksheet Application has been carried out in accordance with applicable regulations. However, the reviewers are challenged in the review stages. The conclusion of this study is that the Worksheet Application to the Regional Government Financial Report review has been going well. Based on the research results, the authors provide advice to the Inspectorate of Karanganyar Regency, the Karanganyar Regency Inspectorate create a Regional Government Financial Report’s review team with members competent in accounting, conduct in-house training and consultation services, prepare standard operational procedure and coordinate with regional finance agency at Karanganyar Regency